MEMAHAMI KOMUNIKASI PENYESUAIAN DIRI ANAK TUNARUNGU DI SEKOLAH INKLUSI - Susilo, Alysha Paxia (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
Deaf and hard-hearing children that goes to inclusive school often find difficulties in adjusting themselves in inclusive school environment. this several factors are affecting this condition including psychosocial, communication, and behavioral factors that they get from the school environment. Communication of anxiety and uncertainty reduction is the early stage of how deaf and hard hearing children can adapt themselves in inclusive school environment. the aim of this research is to understand the narrative of deaf and hard-hearing children of their selfadjustment in inclusive school through their strategy of anxiety and uncertainty reduction. The type of this research is qualitative research. this research analyze and interpret some written text about deaf and hard-hearing children’s experience of adjustment in inclusive school. this research is using Mishler’s narrative analysis. Result of this research shows different narratives of deaf and hard-hearing children’s self adjustment in inclusive school. those narratives are complete withdrawal from school environment, passive observation and only focusing on school subjects. only close with their deaf and hardhearing friendsa, finding close friends that diesnt require any special needs, and the last one which is getting external support from teachers and friends in the inclusive school environment. moreover, they use passive and interactive technique in information-seeking to reduce their uncertainty. they are most likely use multiple modal of communication and highly dependent on the usage of social media as tools to seek information and communicate. in addition, the role of social support from their close relatives is highly affecting their initiatives in reducing anxiety and uncertainty that they experience based on the results, researcher suggests that people that involves in inclusive school settings including parents, teachers, and friends to always support and help children with deaf and hearing-impaired condition physically and psychologically to adapt in inclusive school environments. without significant support and help, initiatives of reducing anxiety and uncertainty will not be effective thus can worsen their self adjustment in inclusive school.Keywords : Deaf and Hard-hearing children, uncertainty and anxiety reduction communication, self adjustment